2020
DOI: 10.1371/journal.pone.0241756
|View full text |Cite
|
Sign up to set email alerts
|

Sit bath systems: A new source of Legionella infection

Abstract: Sit Bath Systems (SBSs) are the most common hygiene method for patients who are not self-sufficient. Therefore, the water quality of SBSs in the nosocomial environment plays a fundamental role in controlling infections for both patients and health-care workers. A long-term study on Legionella and Pseudomonas aeruginosa (P . aeruginosa ) contamination was performed in SBSs (n = 20) of six Health Care Facilities (HCFs). A total of 254 water sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Serogroups 3 and 6 were found in environmental water samples in several studies [ 54 , 80 , 81 , 82 , 83 ]. Particularly, serogroup 3 was isolated in hospitals in Iran [ 84 ], while Pignato et al revealed the prevalence of this serogroup in Italian hospitals, which was sometimes associated with serogroup 6 [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serogroups 3 and 6 were found in environmental water samples in several studies [ 54 , 80 , 81 , 82 , 83 ]. Particularly, serogroup 3 was isolated in hospitals in Iran [ 84 ], while Pignato et al revealed the prevalence of this serogroup in Italian hospitals, which was sometimes associated with serogroup 6 [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these pathogens' presence or absence fails to determine the growth of opportunistic pathogens (OPs), which are usually not of Enteric or Fecal origin (Felfoldi et al, 2010;Mapili et al, 2020). It has also been suggested that the presence of certain other opportunistic pathogen species or other Legionella species in biofilms promote Legionella growth through increased resistance to temperature and disinfectants by horizontal gene transfer (Girolamini et al, 2022). This however is still controversial as studies suggest both an association and a lack thereof between the growth of Legionella and other OPs such as P. aeruginosa (Masaka et al, 2021;Atnafu et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…and extracellularly by harvesting carbon and energy sources excreted by other bacteria (Declerck et al, 2009;Stojek and Dutkiewicz, 2011). Biofilms also provide protection from disinfectants and temperature while serving as a substrate for exchange of genetic material and play a pivotal role in the maintenance of Legionella through the water system as parts of them get detached as a result of many factors such as temperature (Whiley et al, 2019;Calero Preciado et al, 2021;Girolamini et al, 2022).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation